2022
DOI: 10.1101/2022.09.19.508542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthetic maize centromeres transmit chromosomes across generations

Abstract: Centromeres are long, often repetitive regions of genomes that bind kinetochore proteins and ensure normal chromosome segregation. Engineering centromeres that function in vivo has proven to be difficult. Here we describe a LexA-CENH3 tethering approach that activates functional centromeres at maize synthetic repeat arrays containing LexO binding sites. The synthetic centromeres are sufficient to cause chromosome breakage and release of chromosome fragments that are passed through meiosis and into progeny. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Some centromeres do not appear to be composed of one or many clear tandem repeats and their harmonics; instead, they are made up of clusters of retrotransposons. Zea mays (Dawe et al ., 2023) and Triticum monococcum (bread wheat and einkorn wheat (Ahmed et al ., 2023)) are examples of such centromeres (Figure 5E and F). The blur in the Fourier transform implies that the repetitive sequences vary considerably in length.…”
Section: Resultsmentioning
confidence: 99%
“…Some centromeres do not appear to be composed of one or many clear tandem repeats and their harmonics; instead, they are made up of clusters of retrotransposons. Zea mays (Dawe et al ., 2023) and Triticum monococcum (bread wheat and einkorn wheat (Ahmed et al ., 2023)) are examples of such centromeres (Figure 5E and F). The blur in the Fourier transform implies that the repetitive sequences vary considerably in length.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of B Chromosome-derived mini-chromosomes in maize showed that many can also pair and recombine during meiosis, although smaller variants showed precocious separation during anaphase and, in other cases, did not pair (Han et al 2008). In maize, tethering CENH3 using a LexA fusion to an array of LexO repeats causes formation of dicentric chromosomes that show instability and chromosome breakage, with the resulting mini-chromosomes being maintained through subsequent generations (Dawe et al 2023). As these mini-chromosomes can autonomously propagate, they have the potential to form chassis or blueprints for artificial chromosomes capable of delivering complex pathways within and between species (Dawe et al 2023).…”
Section: Cenh3 Genome Elimination and Mini-chromosomesmentioning
confidence: 99%
“…Root tissues were collected from tissue culture-grown 717 plantlets. Fluorescent in situ hybridization and slides preparation were performed following published methods (Dawe et al, 2023), using four 6-FAM-labeled PtaM147 oligos (5 0 -ATCGAAGTCGGAATGCCG CGA-3 0 ,5 0 -AGCAGAAGCATACATGCTCAA-3 0 , 5 0 -AAGGCAACTGAA TTTCGGCAA-3 0 , 5 0 -AACTCACCGAGTCAAAGCGTT-3 0 ). The images were captured using a Zeiss Axio Imager.M1 fluorescence microscope with a 639 plan-apo Chromat oil objective.…”
Section: Fluorescent In Situ Hybridizationmentioning
confidence: 99%